Dye-sensitized Solar Cell (DSSC) Menggunakan Ekstrak Limbah Teh Padat Hasil Pabrik - Ananda Azhari Aprianty Pabo; Milenia Magdalena Kassa; Ariyanti Sarwono; Medlyn Elmitria Tapai; Carolus Aditya Chandra Pratama; Richard Dominggo; I Wayan Koko Suryawan (Jurnal Ilmiah Lingkungan Kebumian, 2022)
As the seventh largest tea producer in tea world, Indonesia generates an estimated total of 137.803 tons in 2019 with large quantities of wastes from tea industries. In this project, zero waste concept was implemented from farm to tea factory to minimize waste generation. Tea objective of this study is to fabricate light trap based on DSSC derived from tea factory waste. Both modified carbon and dyes from tea waste were investigated to develop DSSC prototype using sandwich method by coating TiO2 on ITO (Indium Tin Oxide) glass. The counter electrode and dyes were prepared by calcinating tea plant waste (stem, leaves, etc.). Extracting processed tea waste, respectively leaves used (black tea, green tea, and white tea) and cathode type carbon and strained-iron were compared. Variations in tea thickness of counter modified carbon electrode and area were performed. Tea efficiency and amount of energy generated in tea application of DSSC in light traps was estimated. The best DSSC voltage is found in size of 100 cm2 with a black tea dye of 612.4 mV with an efficiency of 1.2002% using strained-iron electrode.